Kepuasan Masyarakat Terhadap Pelayanan Kelurahan Setelah Pemekaran Di Tangerang Selatan - Pitri Yandri (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2013)
The purpose of this study is (1) to analyze public perception on urban services before and after the expansion of the region, (2) analyze the level of people's satisfaction with urban services, and (3) analyze the determinants of the variables that determine what level of people's satisfaction urban services. This study concluded that first, after the expansion, the quality of urban services in South Tangerang City is better than before. Secondly, however, public satisfaction with the services only reached 48.53% (poor scale). Third, by using a Cartesian Diagram, the second priority that must be addressed are: (1) clarity of service personnel, (2) the discipline of service personnel, (3) responsibility for care workers; (4) the speed of service, (5) the ability of officers services, (6) obtain justice services, and (7) the courtesy and hospitality workers.